Case report: Response to tepotinib in Chinese non-small cell lung cancer patients harboring METex14 skipping with varying features - Meng, Yan; Zhou, Weiping; Li, Chenping; Zhou, Xiangjie; Li, Xiao; Li, Liang; Fu, Qiye; Huang, Jue; Yue, Yali; Shen, Xuguang; Yang, Lijing; Wang, Meiqing (Frontiers in Oncology, 2024)
MET exon 14 (METex14) skipping is the most reported MET mutation in non-small cell lung cancer (NSCLC) and has been confirmed to respond to MET tyrosine kinase inhibitors (TKI) in clinical trials. While MET TKI tepotinib was recently approved for METex14 skipping NSCLC in China, real-world evidence is limited. We report our experience treating NSCLC patients referred from oncology sites across China with tepotinib in the Boao Lecheng Pilot Zone. Four patients have been prescribed the drug with a median age of 67 years (range, 61-71 years). One patient has concomitant BRAF V600E mutation, and another patient had savolitinib as first line of therapy but discontinued due to hepatotoxicity. Till the end of follow-up, four patients were all on tepotinib therapy, with a median duration of therapy of 19 months. One patient achieved partial response and three achieved stable disease. Three patients had peripheral edema, but all were mild. Our experience showed in real clinical setting, tepotinib had robust and durable clinical activity and a favorable toxicity profile in Chinese patients with METex14 skipping NSCLC. It is the first report on the effectiveness of tepotinib in a patient with both METex14 skipping and BRAF V600E mutations and successful MET inhibitor switch after MET inhibitorinduced liver injury.